On semiring complexity of Schur polynomials - Fomin, Sergey; Grigoriev, Dima; Nogneng, Dorian; Schost, Éric (Computational complexity, 2018)
Semiring complexity is the version of arithmetic circuit complexity that allows only two operations: addition and multiplication. We show that semiring complexity of a Schur polynomial s λ ( x 1 , ⋯ , x k ) labeled by a partition λ = ( λ 1 ≥ λ 2 ≥ ⋯ ) is bounded by O ( log ( λ 1 ) ) provided the number of variables k is fixed.